The Translations Of Selected Metaphors In The Stories Of Rostam In Shahname - Bahraman, Mostafa (2014)
This research posits that recognizing and understanding metaphors in the source language (SL) and to reproduce them in the target language (TL) are not an easy task. If a translator does not understand the SL metaphor, s/he may miss the message, and/or transferred an erroneous message into the TL. As semantic novelties, metaphors pose considerable challenge as they are with no immediate equivalents in the TL. One aim of this study is to determine whether the selected translators have recognised metaphors. Mengenalpasti dan memahami metafora dalam teks bahasa sumber (BS) dan menterjemahnya ke dalam bahasa sasaran (BT) merupakan mendasari kajian ini. Jika penterjemah tidak memahami metafora di dalam BS, berkemungkinan penterjemah tidak mendapat mesej sebenar dan/atau memindahkan mesej yang salah ke dalam BT. Metafora mencabar sebagai satu unsur semantik baru yang tidak mempunyai padanan dalam BT. Tujuan utama kajian ini ialah untuk memastikan bahawa penterjemah dapat mengenal pasti metafora.